Molecular and phenotypic characteristics of T1 transgenic yellow cosmos (Cosmos sulphureus) carrying neomycin phosphotransferase II gene (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Irsyadi MB, Sawitri WD, Purwantoro A. 2022. Molecular and phenotypic characteristics of T1 transgenic yellow cosmos (Cosmos sulphureus) carrying neomycin phosphotransferase II gene. Biodiversitas 23: 6097-6105. Yellow cosmos (Cosmos sulphureus) is a tropical ornamental flower that contains secondary metabolites useful fornatural pesticide application. Plant genetic transformation is one genetic engineering method used to increase secondary metabolite accumulation. However, published reports on this issue have yet to be made available. This is the first report of genetic transformation in transgenic yellow cosmos using neomycin phosphotransferase II (nptII) encoding gene. This study aimed to determine the efficiency transformation and phenotypic character of the T1 yellow cosmos transgenic nptII. This genetic transformation was carried out by the floral dip method mediated with Agrobacterium tumefaciens and characterized based on quantitative and qualitative observations, as well as a cluster analysis of transgenic plants. The T1 transgenic yellow cosmos was confirmed using PCR with a transformation efficiency of 73.33% based on the total plants resistant to Kanamycin and 10.57% based on the total seeds transformed. The presence of the nptII encoding gene was shown in transgenic plant samples with a size of 550 bp. In general, the introduction of the nptII gene generated no novel traits except the resistance to the kanamycin antibiotic. However, there was a decrease and increase in the number of stomata and the size of stomata in transgenic plants, respectively. In addition, there was a change in the type of ray floret to a mixture of ligulate and tubular, indicating that the nptII gene affected the phenotype of yellow cosmos. The result revealed that the nptII gene was inserted fairly randomly into the plant genome.
Keywords: Cosmos, nptII, phenotypic, transgenic